The contribution of short time delayed echoes to the intelligibility of speech and its significance in architectural acoustics - Burger, Johannes Francois (Department of Electrical Engineering, 2016)
The investigation covered various aspects of the effects of a single delayed echo on the intelligibility of speech and was extended to cover the case of multiple echoes which is more in line with practical conditions than a single echo. The application of the results obtained to architectural acoustics and speech reinforcement is discussed.